Energy system contribution in XC skiing: theoretical framework and practical application for sprint and distance skiing - Losnegard, T. (Nordic Winter Sports Conference, 2020)
Energy system contribution during cross-country (XC) skiing races is dependent on several factors, including the race duration, track profile, and sub-techniques applied, and their subsequent effects on the use of the upper and lower body. During both sprint (=1.8 km) and distance races (=10 and 15 km, women and men, respectively) a high aerobic turnover interacts with subsequent periods of very high work rates at ~120 to 160% of VO2peak during the uphill sections of the race. The repeated intensity fluctuations are possible due to the nature of skiing, which involves intermittent downhills where skiers can recover. Thus, the combination of high and sustained aerobic energy turnover and repeated work rates above VO2peak, interspersed with short recovery periods, distinguishes XC skiing from most other endurance sports. The overall annual training of elite skiers, both in sprint and distance skiing, has been widely studied over the last decades. Moreover, several studies have demonstrated that male and female world-class skiers are among the endurance athletes with the highest VO2max. Accordingly, world-class performance has been associated with maximal values above 70 and 80 mL/kg/min, in female and male skiers, respectively. However, an important but unsolved question is how to optimize training to enhance the recovery of the energy reserve during intermittent exercise, which is possible whenever the O2-demand is lower than the "critical power". This ability is probably a prerequisite for achieving a World class level, and potentially be a significant principle in a tapering process leading up to important competitions.